The unsung great : stories of extraordinary Japanese Americans - Robinson, Greg, 1966- (Scott and Laurie Oki series in Asian American studies., 2020)
"From a title-winning boxer in Louisiana to a Broadway baritone in New York, Japanese Americans have long belied their popular representation as "quiet Americans." Showcasing the lives and achievements of relatively unknown but remarkable people in Nikkei history, scholar and journalist Greg Robinson reveals the diverse experiences of Japanese Americans and explores a wealth of themes, including mixed-race families, artistic pioneers, mass confinement, civil rights activism, and queer history. Drawn primarily from Robinson's popular writings in the San Francisco newspaper Nichi Bei Weekly and community website Discover Nikkei, The Unsung Great offers entertaining and compelling stories that challenge one-dimensional views of Japanese Americans. This collection breaks new ground by devoting attention to Nikkei beyond the West Coast-including the vibrant communities of New York and Chicago, as well as the little-known history of Japanese Americans in the US South. Expertly researched and accessibly written, The Unsung Great brings to light a constellation of varied and incredible life stories"--